Digital Transformation in Tourism Education: Driving Forces and Challenges - Ayuba, Hasan (English Education Department, 2024)
This systematic literature review examines the implementation of digital transformation in tourism and hospitality education through an analysis of 20 peer-reviewed articles published between 2019-2024. The study employs a rigorous methodological approach involving systematic database searches, strict inclusion-exclusion criteria, and qualitative content analysis to identify key themes, implementation challenges, and strategic recommendations. The findings reveal a significant disparity in digital transformation implementation between developed and developing nations. While developed countries primarily focus on optimizing technological utilization and pedagogical innovation, developing nations face fundamental challenges including inadequate infrastructure and pronounced digital divides. The analysis identifies several development opportunities, including enhanced learning flexibility, improved digital literacy, and the integration of advanced technologies such as AI and IoT in tourism education. The study's practical implications emphasize the importance of establishing robust digital frameworks, implementing comprehensive educator training programs, and adapting curricula to achieve an optimal balance between technological and practical learning components. This research contributes to the theoretical understanding of digital transformation in tourism education while suggesting future research directions to evaluate the long-term effectiveness of hybrid learning models across various geographical and socio-economic contexts. The findings provide valuable insights for educational institutions, policymakers, and industry stakeholders in developing strategies for effective digital transformation in tourism education. Keywords: Digital transformation; tourism education; e-learning; systematic literature review; hybrid learning